Systematic review of patient-reported outcome measures in patients with varicose veins. Issue 11 (3rd August 2017) - Aber, A; Poku, E; Phillips, P; Essat, M; Buckley Woods, H; Palfreyman, S; Kaltenthaler, E; Jones, G; Michaels, J
Abstract: Background: Varicose veins can affect quality of life. Patient-reported outcome measures (PROMs) provide a direct report from the patient about the impact of the disease without interpretation from clinicians or anyone else. The aim of this study was to examine the quality of the psychometric evidence for PROMs used in patients with varicose veins. Methods: A systematic review was undertaken to identify studies that reported the psychometric properties of generic and disease-specific PROMs in patients with varicose veins. Literature searches were conducted in databases including MEDLINE, up to July 2016. The psychometric criteria used to assess these studies were adapted from published recommendations in accordance with US Food and Drug Administration guidance. Results: Nine studies were included which reported on aspects of the development and/or validation of one generic (36-Item Short Form Health Survey, SF-36®) and three disease-specific (Aberdeen Varicose Vein Questionnaire, AVVQ; Varicose Veins Symptoms Questionnaire, VVSymQ®; Specific Quality-of-life and Outcome Response – Venous, SQOR-V) PROMs. The evidence from included studies provided data to support the construct validity, test–retest reliability and responsiveness of the AVVQ. However, its content validity, including weighting of the AVVQ questions, was biased and based on the opinion of clinicians, and the instrument had poor acceptability. VVSymQ® displayed good responsiveness and acceptability rates. SF-36® was considered to have satisfactory responsiveness and internal consistency. Conclusion: There is a scarcity of psychometric evidence for PROMs used in patients with varicose veins. These data suggest that AVVQ and SF-36® are the most rigorously evaluated PROMs in patients with varicose veins. Abstract : AVVQ and SF-36 good options